ANALISIS PENGUKURAN KINERJA DENGAN PENDEKATAN VALUE FOR MONEY PADA KANTOR KEMENTRIAN AGAMA KABUPATEN POSO TAHUN 2013-2014 - Pancanugraha, Indra (Katalogis, 2017)
This research aims to anlyze the performance of the Department of Religious Affairs of Poso in 2013 to 2014 with Value For Money Approach based on the elements of economy, efficiency, and effectiveness. Based on the value for money approach from economics aspect, the department of religious affairs has been conducting its programs economically, these include: managerial support program and other technical issues, Islamic community guidance program, Islamic education program, Christian community guidance program, and program of hajj and umroh. All these programs achieved their objectives eccept program of hajj and umroh, which output is not reached. Performance from efficiency element shows that the office has been running its programs efficiently, program of managerial support program and the other technical issue, and Islamic community gudance program have achieved their output; Islamic education program and Christian comunity guidance program has been running quite efficiently with output performance achieved; meanwhile, program of hajj and umroh has been running highly efficient but the output is unreached. The results from effectiveness element show that the office of religious affairs has been running its program pretty efective;these include managerial support and other technical issues; while Islamic community guidance, Islamic education program and Christian guidance program are efectively implemented; program hajj and umroh is inefective.